GIMAP6 is required for T cell maintenance and efficient autophagy in mice - John C. Pascall; Louise M. C. Webb; Eeva-Liisa Eskelinen; Silvia Innocentin; Noudjoud Attaf-Bouabdallah; Geoffrey W. Butcher (PUBLIC LIBRARY SCIENCE, 2022)
The GTPases of the immunity-associated proteins (GIMAP) GTPases are a family of proteins expressed strongly in the adaptive immune system. We have previously reported that in human cells one member of this family, GIMAP6, interacts with the ATG8 family member GABARAPL2, and is recruited to autophagosomes upon starvation, suggesting a role for GIMAP6 in the autophagic process. To study this possibility and the function of GIMAP6 in the immune system, we have established a mouse line in which the Gimap6 gene can be inactivated by Cre-mediated recombination. In mice bred to carry the CD2Cre transgene such that the Gimap6 gene was deleted within the T and B cell lineages there was a 50-70% reduction in peripheral CD4(+) and CD8(+) T cells. Analysis of splenocyte-derived proteins from these mice indicated increased levels of MAP1LC3B, particularly the lipidated LC3-II form, and S405-phosphorylation of SQSTM1. Electron microscopic measurements of Gimap6(-/-) CD4(+) T cells indicated an increased mitochondrial/cytoplasmic volume ratio and increased numbers of autophagosomes. These results are consistent with autophagic disruption in the cells. However, Gimap6(-/-) T cells were largely normal in character, could be effectively activated in vitro and supported T cell-dependent antibody production. Treatment in vitro of CD4(+) splenocytes from GIMAP6(fl/fl) ERT2Cre mice with 4-hydroxytamoxifen resulted in the disappearance of GIMAP6 within five days. In parallel, increased phosphorylation of SQSTM1 and TBK1 was observed. These results indicate a requirement for GIMAP6 in the maintenance of a normal peripheral adaptive immune system and a significant role for the protein in normal autophagic processes. Moreover, as GIMAP6 is expressed in a cell-selective manner, this indicates the potential existence of a cell-restricted mode of autophagic regulation.